SuperJoe does not do cuddles - Catchpool, Michael (Lantana, 2021)
SuperJoe is convinced he doesn't need cuddles from his mom. He flies around the neighborhood rescuing people from escaped tigers, runaway trains and raging rivers, all while battling his nemesis the Gray Shadow. Naturally, he refuses all cuddles. Until, one night, when he can't sleep...